2020
DOI: 10.3390/met10121625
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Virgin and Recycled 316L SS and AlSi10Mg Powders Used for Laser Powder Bed Fusion Additive Manufacturing

Abstract: In this study, the comparison of properties between fresh (virgin) and used (recycled) 316L stainless steel (316L SS) and AlSi10Mg powders for the laser powder bed fusion additive manufacturing (L-PBF AM) process has been investigated in detail. Scanning electron microscopy (SEM), electron-dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) techniques are used to determine and evaluate the evolution of morphology, particle size distribution (PSD), circularity, chemical composition, and phase (crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 91 publications
1
8
0
Order By: Relevance
“…As shown in figure 5(d), a typical XRD pattern of the single γ-austenite FCC structure was observed at the SS part, similar to that of LPBF-printed SS reported in a previous study [47]. Four major peaks in the diffraction pattern (figure 5(c)) of the LPBF-printed W region was the same as the original pure BCC W powder [48].…”
Section: Xrd Of Materials Interfacessupporting
confidence: 82%
“…As shown in figure 5(d), a typical XRD pattern of the single γ-austenite FCC structure was observed at the SS part, similar to that of LPBF-printed SS reported in a previous study [47]. Four major peaks in the diffraction pattern (figure 5(c)) of the LPBF-printed W region was the same as the original pure BCC W powder [48].…”
Section: Xrd Of Materials Interfacessupporting
confidence: 82%
“…The tests show that the mean circularity value of the produced particles is always higher than 0.8 (see Table 6), indicating an extensive spheroidization of the powders whatever the raw powder processed (where as spheroidization is meant the percentage of particles whose circularity is over 0.8). According to the literature [24,25], it is recommended that the circularity factor required for powders to be considered for further reuse in AM would be as close to 1 as possible, or at least ≥0.7. Indeed, it is worth noting that, for example, for the A3 test, a spheroidization degree of 85% means that more than 85% of the particles can be used for AM application.…”
Section: Resultsmentioning
confidence: 99%
“…The PSD became narrower since finer particles pass through the gap and spread while larger ones is pushed away with the blade from the build plate. Therefore, a narrower PSD with increased number of large particles and decreased number of fine particles is achieved with recycling powders in PBF method [131].On the other hand, in some articles such as Yusuf et al it is suggested that the PSD of recycled 316L SS in SLM method is not noticeably changed compare to the virgin batch [132]. This may be due to the reason that the gap size is large enough to spread the coarse particles along with the finer ones.…”
Section: Particle Size and Size Distributionmentioning
confidence: 99%